Industrial training report: Universiti Tenaga Nasional (UNITEN), Information Resource Centre (IRC) / Nurul Hanis Ahmad Murad - Ahmad Murad, Nurul Hanis (Faculty of Information Management, 2019)
Industrial Training, IMC690, is a mandatory subject that students of Library Management, IM244, need to undergo for five (5) months at an organization of their choice that are approved by the faculty. Objectives of the training is to provide preprofessional work experience to trainees under the supervision of the faculty and industry. Trainee has selected UNITEN IRC, an academic library, as the place for the industrial training. While trainee was undergoing training there, trainee was under the supervision of Sir Ridzuan Ibrahim, from the faculty, and Mrs. Khairun Fasehah Abd Halim, from the industry. For five months of the industrial training, trainee had rotation of units as conditioned by the faculty to enable trainee to learn and practices all the unit's task and workflow. Trainee started with Admin and e-Resources Unit, Resource Development Unit, Serials and Repository Unit, Reference and Information Service Unit, User Services Unit, and Technical Process Unit. By the end of the training, trainee is expected to have gained knowledge and present their lesson learnt as well as details on their special project executed during the industrial training.